On Stability of Nonautonomous Perturbed Semilinear Fractional Differential Systems of Order α∈(1,2) - Mohammed M. Matar; Esmail S. Abu Skhail (Journal of Mathematics)
We study the Mittag-Leffler and class-K function stability of fractional differential equations with order α∈(1,2). We also investigate the comparison between two systems with Caputo and Riemann-Liouville derivatives. Two examples related to fractional-order Hopfield neural networks with constant external inputs and a marine protected area model are introduced to illustrate the applicability of stability results.